PUBLIC PERCEPTION AND ADAPTATION TOWARDS CLIMATE CHANGE POLICY IN MALAYSIA - Phaik Nie, Chin; Punitha, Jayapalan; Yashar, Salamzadeh, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study examined the relationship between public risk perception, public awareness, public knowledge and public adaptation towards climate change policies in Malaysia, with attitude towards climate change as the mediator. This study adopted selfadministered online questionnaires to collect inputs from Malaysians across all states. A total of 200 usable data was analysed in this study. The SPSS was used for the descriptive statistics analysis and SmartPLS was used for the measurement model and structural model analysis. Based on the findings, the results show that public risk perception has a significant effect on public adaptation towards climate change. Besides, public attitude mediates the relationship between public risk perception and adaptation towards climate change policy. These results will be useful for the government and industries in understanding public perceptions and attitudes towards climate change policies initiated by the government. Thus, it provides insights for the government in formulating climate change policy.